Political learning and identity of first-time Filipino voters influence of knowledge, values, attitudes, and action - Enginco, Marcial L.
The rise of Facebook and video-streaming channels TikTok and Youtube as quick and efficient sources of political information calls into question the relevance of more traditional sources of political socialization such as the home, school, and conventional information outlets like newspapers, radio, and TV in shaping political identity in youth. This paper investigates how first-time voters born after 2000 learn their political identity and what factors influence such development. Using narrative research, ten interlocutors, aged 19-23 years old, were purposively selected to share, through a semi-structured interview, their knowledge, views, and experiences relating to the elections and the socio-political issues relevant to the times. It has been found that families seldom talk about politics in the household in favor of more pressing personal concerns and teachers avoid discussing politics inside the classroom to avoid potential conflicts. Overall, the school system is programmed to focus on academics to prepare students to be productive members of society, at the expense of honing citizenship. Thematic analysis of the data led to the development of the Knowledge Values Attitudes Action (KVAA) Pathway to Political Learning, which identifies political knowledge and personal values as the foundation for building attitudes that trigger a specific action in any given political decision. Further analysis of the KVAA model has led to the development of a Political Learner Identity Status (PLIS) model, with the Political Sophisticate as the ideal of a politically independent individual. Both the KVAA and PLIS models can serve as the bedrock on which future studies on political identity learning, a largely unexplored domain, can be built.